The Role of Phonetics in Improving Pronunciation Skills in Second Language Acquisition - Indi Hanifah Ramadani Siregar; Naila Alzahwa (JELT : Journal of English Education, Teaching and Literature, 2025)
The Phonetics play a vital role in improving Pronunciation in Second Language Acquisition (SLA) process. Phonetics is the scientific study of spoken language where it provides an analysis of spoken language. It is the branch where the phonological processes of the language are studied. It is a part of phonological analysis that enables the second language learners to master the pronunciation process.